DESIGN IMPROVEMENT OF A 2 MVA SYNCHRONOUS MACHINE BY USING PARTICLE SWARM OPTIMIZATION - Doğan, Kıvanç; Orhan, Ahmet (Zülküf GÜLSÜN [EN], 2022)
In this article; The step-by-step design of a 3-phase salient synchronous generator and efficiency optimization with particle swarm optimization technique are investigated. Unlike other studies in the literature, a system has been studied to minimize mathematical equation errors by using specific loading parameters that simplify the design process. It has been tried to obtain a program structure that minimizes programming problems by minimizing the number of variables used in the design. With the optimization of the specific loading parameters, the effects on the machine volume, cost and efficiency were examined.
Keywords: Electrical Engineering; Elektrik Mühendisliği